2017
DOI: 10.1080/01902148.2017.1385110
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary NaCl affects bleomycin-induced lung fibrosis in mice

Abstract: Purpose High levels of NaCl in the diet are associated with both cardiac and renal fibrosis, but whether salt intake affects pulmonary fibrosis has not been examined. Aim of the Study To test the hypothesis that salt intake might affect pulmonary fibrosis. Materials and Methods Mice were fed low, normal, or high salt diets for 2 weeks, and then treated with oropharyngeal bleomycin to induce pulmonary fibrosis, or oropharyngeal saline as a control. Results As determined by collagen staining of lung sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
6
1
Order By: Relevance
“…This effect could not be seen in SD rats due to the aforementioned limitations of our study design; however, increased levels of total CD11b/c in granulocytes and CD3+ lymphocytes, together with the slightly increased frequency of CD11b/c-bearing lymphocyte subpopulations, support the conclusion that the HS diet activates PBL leading to leukocyte adhesion and migration, as well other effector mechanisms involved in inflammation [51]. For example, in the model of bleomycin-induced lung fibrosis, it has been shown that the LS diet normalizes leukocyte numbers and decreases CD11b- and CD11c-expressing cells in the lungs of mice [52]. Contrary to our findings in humans, the aHS group of rats presented with increased CD11a expression in PBL, but similarly to the human study, the frequency of certain highly CD11a-positive cells was decreased, suggesting their transmigration to the sites of inflammation.…”
Section: Discussionmentioning
confidence: 72%
“…This effect could not be seen in SD rats due to the aforementioned limitations of our study design; however, increased levels of total CD11b/c in granulocytes and CD3+ lymphocytes, together with the slightly increased frequency of CD11b/c-bearing lymphocyte subpopulations, support the conclusion that the HS diet activates PBL leading to leukocyte adhesion and migration, as well other effector mechanisms involved in inflammation [51]. For example, in the model of bleomycin-induced lung fibrosis, it has been shown that the LS diet normalizes leukocyte numbers and decreases CD11b- and CD11c-expressing cells in the lungs of mice [52]. Contrary to our findings in humans, the aHS group of rats presented with increased CD11a expression in PBL, but similarly to the human study, the frequency of certain highly CD11a-positive cells was decreased, suggesting their transmigration to the sites of inflammation.…”
Section: Discussionmentioning
confidence: 72%
“…High-salt intake induces a chronic low-grade inflammation promoting not only hypertension (12), kidney damage (13), and cardiovascular disease (14) but also a more severe outcome in a number of inflammatory diseases (15)(16)(17)(18). This association appears to be related, at least in part, to the ability of sodium to modulate the function of either innate and adaptive immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is thus an urgent need for identification of dietary targets to prevent or limit intestinal fibrosis. Indeed, Western diet promotes fibrosis in studies from other organs 17 , 18 . Western diet is characterized by an insufficient intake of healthy foodstuffs and an excessive amount of saturated fats, sugar and salt.…”
Section: Discussionmentioning
confidence: 99%